Localized Market Power in the U.S. Airline Industry - Evans, William N.; Kessides, Ioannis N. (The Review of Economics and Statistics, 1993)
This paper tests whether the observed dominance of most city-pair markets and airports in the U.S. domestic airline industry by single carriers confers any pricing power on the dominan t firms. The results of fixed-effects estimation indicate that airport dominance by a carrier does confer upon it substantial pricing power , whereas dominance at the route level seems to confer no such pricing power. Additionally, the authors find a positive, yet small, correlation between both route concentration, and price and airport concentration and price. The quantitative importance of airport dominance reveals that the most promising direction for public polic y aimed at improving the industry's performance is to ensure equal acc ess to sunk airport facilities.